Histopathological spectrum of disorders of sexual development: a case series of seven cases - Bolde, Saroj Ashok; Pirosha, Arva Ali; Ramraje, Sushma N.; Agale, Shubhangi V. (International Journal of Research in Medical Sciences, 2020)
Disorders of sexual development (DSD) refer to cases in which there is a discordance among at least two of the following; genetic sex, gonadal sex, genital tract sex and phenotypic sex. DSDs are quite rare with reported incidence varying from 1 in 4,500 to 1 in 5,500. Ovotesticular disorder is amongst the rarest variety of DSD comprising only to 3-10% of all cases of DSD with only 500 cases reported till now worldwide. Frequency of MRKH syndrome is 1 in 4,500 cases and is the cause of amenorrhoea in 15% of cases of primary amenorrhoea. Authors present a case series of seven cases of DSDs with three cases diagnosed as androgen insensitivity syndrome, two cases of true ovotesticular DSD (true hermaphrodite), one case each of mixed gonadal dysgenesis and Mayer-Rokitansky-Kuster Hauser (MRKH) syndrome. Authors received the histopathology specimen of these cases in this department which was extensively sampled to study the gonads and the other derivatives of Mullerian and Wolffian duct and to rule out presence of any malignancy.